A Computer Aided Study of the Vehicle’s Suspension System and a Determination of its Optimal Specifications - كفا سمير; النجار رائد; طحان فادي (Latakia University Journal -Engineering Sciences Series, 2020)
This study describes the analysis of a suspension system and its upper and lower arm with a spring. The analyses are performed using Autodesk Inventor Professional software package to determine the stress behavior during the course of operation for the components of the suspension system. The suspension is considered one of the important component parts of the vehicle and it is directly affect safety, performance, noise level and driving comfort. The primary aim of this study is to minimize the applied load on the suspension system in order to limit the build-up stresses during the course of operation. Moreover, the stress created by the road is directly related to the lower arm of the suspension system. Therefore, this study investigates the parameters for the ideal design of the suspension system to minimize the impact of stresses that are imposed by the road. To analyze stresses, the loading conditions for the lower and upper arms should be determined beforehand. Therefore, a double wishbone suspension system model is used for analysis where the obtained results are used for identifying the dynamic status of the lower and upper arms when the system is in operation.